The Gender Wage Gap among College Graduates in Italy - Daniela Piazzalunga (Institute of Labor Economics (IZA), 2017)
The paper investigates the gender wage gap among recently graduated people, controlling for job and academic variables and for the field of study, as women lag in highly remunerative majors. The raw gender gap in hourly wages is 5.6%. Although including academic variables and the field of study, on top of job-related variables, slightly reduces the unexplained gap, the latter still accounts for most of the total difference. Using quantile decomposition, the paper shows that the unexplained gap increases along the wage distribution, indicating a glass ceiling effect. Heterogeneities arise across fields of study: the largest total gap emerges in Law, Political-Social sciences, and Economics-Statistics. In most disciplines, there is a significant unexplained gap – from 3.3% (Medicine), to 8.7% (Law), up to 9.6% (Agriculture) – which constitutes the largest share of the difference, confirming that most of the wage gap remains unexplained also by major. Finally, I use geographical differences to explore the influence of institutional and macro-economic variables, as well as of attitudes towards gender norms. Results indicate that childcare and part-time availability are correlated with lower gender wage gaps, while traditional gender norms are associated with higher gaps.
Keywords: J16; J31; J71; 330; gender wage gap; Oaxaca-Blinder decomposition; college graduates; quantile decomposition; field of study; regional differences